QARAQALPAQ TILIN AVTOMATIK TÚRDE ANALIZLEWDE MASHINALÍQ OQÍTÍW ALGORITMLERIN QOLLANÍLÍW - Abdalieva, G.R.; Uteuliev, N.U.; Kalmuratov, B.K. (SCIENCE and SOCIETY, 2025)
This article explores the application of machine learning algorithms for the automatic analysis of the Karakalpak language. It describes the processes of automated analysis, including morphology, syntax, and semantics, and examines the technical capabilities of the algorithms. The creation and analysis of language corpora using Python programming and its libraries are highlighted.
Keywords: karakalpak language; automatic analysis; machine learning; natural language processing; morphological analysis; syntactic analysis; semantic analysis; lemmatization; tokenization; technological development; language corpus; Python programming; NLTK; scikit-learn; classification algorithms; language resources